2011
DOI: 10.1093/humrep/der208
|View full text |Cite
|
Sign up to set email alerts
|

IVF and endometriosis-related symptom progression: insights from a prospective study

Abstract: IVF does not expose women to a consistent risk of endometriosis-related symptoms progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 18 publications
3
55
1
3
Order By: Relevance
“…Benaglia et al. also failed to detect any significant pain recurrence during IVF , but this series comprised only nine women with DIE, and the number of patients with bowel involvement and the criteria for conservative treatment were not specified. In addition, the nodules were quite small in size (average 10 mm).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Benaglia et al. also failed to detect any significant pain recurrence during IVF , but this series comprised only nine women with DIE, and the number of patients with bowel involvement and the criteria for conservative treatment were not specified. In addition, the nodules were quite small in size (average 10 mm).…”
Section: Discussionmentioning
confidence: 96%
“…In accordance, early reports indicated that IVF in DIE patients can result in bowel or ureter stenosis , although the precise mechanism is unknown. Subsequent prospective studies have not provided evidence of symptomatic progression during IVF treatment , but this discrepancy could reflect less advanced disease in the study populations.…”
Section: Introductionmentioning
confidence: 96%
“…Number of COH and IVF cycles has not been associated with an increased risk of disease recurrence [46,47].…”
Section: Embryo/egg Freezingmentioning
confidence: 99%
“…There is no evidence to suggest that hormonal treatment prior to IVF in those patients increases the risk of recurrence of the disease. 23 Despite the widespread use of alternative and complimentary medicine among patients with endometriosis, there are no available highquality studies to provide evidence strong enough to advise with or against the use of such remedies.…”
Section: Treatmentmentioning
confidence: 99%